2017
DOI: 10.18632/oncotarget.18032
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome analysis reveals a role for the endothelial ANP-GC-A signaling in interfering with pre-metastatic niche formation by solid cancers

Abstract: Cancer establishes a microenvironment called the pre-metastatic niche in distant organs where disseminated cancer cells can efficiently metastasize. Pre-metastatic niche formation requires various genetic factors. Previous studies suggest that inhibiting a single niche-factor is insufficient to completely block pre-metastatic niche formation especially in human patients. Here we show that the atrial natriuretic peptide (ANP), an endogenous hormone produced by the heart, inhibits pre-metastatic niche formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Nojiri et al reported that, in a large-scale observational clinical study, the perioperative administration of low-dose human ANPs reduced inflammatory responses and postoperative cardiopulmonary complications in patients receiving surgical treatment for lung cancer [ 82 , 83 ]. Interestingly, patients treated with ANPs had longer 2-year relapse-free survival times [ 84 ]. In the lungs of tumor-bearing mice, a significant inactivation of the ANP–NPRA pathway was noticed at the pre-metastatic niche, and ANP treatment downregulated pre-metastatic niche factors, thus preventing lung metastasis [ 84 ].…”
Section: Anti-cancer Effects Of Anpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nojiri et al reported that, in a large-scale observational clinical study, the perioperative administration of low-dose human ANPs reduced inflammatory responses and postoperative cardiopulmonary complications in patients receiving surgical treatment for lung cancer [ 82 , 83 ]. Interestingly, patients treated with ANPs had longer 2-year relapse-free survival times [ 84 ]. In the lungs of tumor-bearing mice, a significant inactivation of the ANP–NPRA pathway was noticed at the pre-metastatic niche, and ANP treatment downregulated pre-metastatic niche factors, thus preventing lung metastasis [ 84 ].…”
Section: Anti-cancer Effects Of Anpsmentioning
confidence: 99%
“…Interestingly, patients treated with ANPs had longer 2-year relapse-free survival times [ 84 ]. In the lungs of tumor-bearing mice, a significant inactivation of the ANP–NPRA pathway was noticed at the pre-metastatic niche, and ANP treatment downregulated pre-metastatic niche factors, thus preventing lung metastasis [ 84 ]. Therefore, the ANP–NPRA pathway may have potential therapeutic value in preventing the pre-metastatic niche formation of solid cancers.…”
Section: Anti-cancer Effects Of Anpsmentioning
confidence: 99%
“…6 Furthermore, a novel therapeutic potential of ANP in cancer treatment has been reported by Nojiri et al, who demonstrated that the recurrence of lung cancer after surgery was significantly lower in ANPtreated patients than in the patients who were not treated with ANP; 3 this is because of the activation of GC-A by ANP. 4 However, the current clinical use of ANP is limited to the continuous intravenous infusion owing to its short half-life (2.4 ± 0.7 min). 5 Thus, the development of a long-acting GC-A activator as an ANP derivative will broaden the clinical use of ANP, including outpatient therapy (which will improve the QOL of patients), heart failure treatment, and metastasis control.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Oishi et al reported its potential application in the treatment of chronic heart failure, using a natriuretic peptide derivative . Furthermore, a novel therapeutic potential of ANP in cancer treatment has been reported by Nojiri et al, who demonstrated that the recurrence of lung cancer after surgery was significantly lower in ANP-treated patients than in the patients who were not treated with ANP; this is because of the activation of GC-A by ANP . However, the current clinical use of ANP is limited to the continuous intravenous infusion owing to its short half-life (2.4 ± 0.7 min) .…”
Section: Introductionmentioning
confidence: 99%